0720 Study of Serum Adiponectin and Resistin in Patients with Obstructive Sleep Apnea. (27th May 2020) - Gharraf, H S; Zidan, M H; Ayad, M W
Abstract: Introduction: The syndrome of OSA is a very common disorder with several important complications and is still under diagnosed. Obesity is considered to be a chronic disease rather than a life style b. Adipose tissue secretory function is disturbed by chronic intermitted hypoxia occurring in OSA. The aim of this study was to study the level of serum adiponectin and resistin in patients with OSA and we tried to assess their association to different parameters of SDB as well as concomitant co morbidities in each patient Methods: This study contained two groups. Patients (group1) included 30 newly diagnosed OSA patients; controls (group 2) included 15 healthy volunteers. All patients were subjected to overnight polysomnography, routine laboratory investigations, Spirometry and fasting serum adiponectin and resistin Results: Patients had statically significant lower serum adiponectin level than controls while serum resistin levels were statistically significant higher in patients than controls also serum adiponectin levels were significantly decreased with increase severity of OSA while serum resistin levels were increased significantly with increase severity of OSA, moreover there was a statistical significant decrease in serum adiponectin levels in patients group with increasing number of comorbidities existing in every patient a. There was a statistical significant increase in serum resistin levels in patients group with increasing number of comorbidities existing in every patient Conclusion: this highlights the possible relationship of these hormones to the metabolic complications seen in OSA patients Support: no conflict of interest